PKK Members Empowerment Through Fashion and Handicraft Creative Industries - Manzilati, Asfi; Priharsanti, Amelia (Universitas Brawijaya, Indonesia, 2012)
Women have potential effect to support their family economies. PKK organization is one of government women empowerment program that in reality depend on government regulation, quite strong control, and practically only used as a dasawisma saving club. On the other hand creative industry especially fashion and handicraft have big opportunity for economic development. Creative industries have become increasingly attractive for women because the activities do not interrupt the domestic area, relate to their hobbies, and do not require high capital. Therefore entrepreneurship on creative industry begins to be an alternative or even solution to increase family economies via PKK members. This means that entrepreneurship program needs to be encouraged in order to increase the potential of PKK organization.